El liberalismo y la burguesía golpista en la Argentina: las propuestas políticas, económicas y sociales del Consejo Empresario Argentino y de la Comisión de Enlace, 1966-1976 - Gonzalo Sanz Cerbino (Les Cahiers ALHIM)
This paper analyze the political, economic and social proposals of business corporations representing the interests of the agricultural and industrial bourgeoisie in the Argentina in the 1960s and 1970s. We will focus on two organizations that have been little-studied: Consejo Empresario Argentino and Comisión de Enlace. Through a comparative analysis of representative documents and testimonies of both groups, we seek to detect the points at which its proposals agreed and those which diverged. This analysis will show that, against the dominant interpretations, these groups have no ideological coincidence around liberal ideas. In this way, we seek to demonstrate that the confluence of both sectors in supporting dictatorial regimes stage, does not respond to the existence of a common platform.